La estructura de tramas paralelas y el nacimiento del cine - Sarmiento Herencia, Diego Alonso (2019)
Cinema is a multifaceted phenomenon and, as such, is really difficult to explain. The processes involved, the diverse elements playing important parts in the development of stories —characters, images, sounds, etc.— are so many and so different that to pretend to explain or define them would be an idle chore. However, in analyzing the works of an individual artist, we find cracks from where faint lights show us how this fabrication happens; the artistry. In that way we can find a common ground gaining the possibility to theorize a process. This paper aims at discovering the relations between cinema and literature, from an structural point of view, using history to determine a common place and the birthplace of the techniques that produce modern cinema.